Asuhan Keperawatan Klien yang Mengalami Pola Nafas Tidak Efektif dengan Bronkopneumonia di Rumah Sakit Budi Lestari Bekasi - Gergika Gentar; Siti Rukayah (Jurnal Persada Husada Indonesia, 2022)
Bronchopneumonia is a pneumonia caused by various etiologies such as bacteria, viruses, fungi, and foreign objects. The purpose of this study is to get a description of the application of nursing care to clients who experienced an ineffective breath pattern with bronchopneumonia at Budi Lestari Hospital Bekasi on 16-18 April 2018. This study used a qualitative research design descriptive approach case study with intervention. Participants in this case are two parent child clients, 2 two family and 1 room nurse. Clients who are the subject of this study are clients who are diagnosed in medical bronchopneumonia and breathing nursing problems are not effective. The result of the research shows that based on the result of the study, there are 3 client nursing diagnoses 1, the ineffective breath pattern, the increase of body temperature and 3 nutritional risk is less than the body requirement and 3 nursing diagnoses on client 2 the ineffective breath pattern, the increase of body temperature and 3 less nutritional risk of body needs. The main intervention given is to examine the frequency / depth of breathing and chest movement. respiration d. After doing nursing action on client 1 obtained three nursing diagnoses with the criterion of the problem resolved that is showing the behavior of pattern of patent breath and vesicular sound, no dyspnea or cyanosis. While the client 2 obtained 3 nursing diagnoses with the criteria of the problem resolved, which shows the behavior of patent breath pattern and vesicular breath sounds, no dyspnea or cyanosis. The results of the action to examine the frequency / depth of breathing and chest movement, vesicular breathing was not using respiratory muscles.